Vulnerability of the biota in riverine and seasonally flooded habitats to damming of Amazonian rivers - Latrubesse, Edgardo M.; d'Horta, Fernando M.; Ribas, Camila C.; Wittmann, Florian; Zuanon, Jansen; Park, Edward; Dunne, Thomas; Arima, Eugenio Y.; Baker, Paul A. (Aquatic conservation, 2021)
The extent and intensity of impacts of multiple new dams in the Amazon basin on specific biological groups are potentially large, but still uncertain and need to be better understood. It is known that river disruption and regulation by dams may affect sediment supplies, river channel migration, floodplain dynamics, and, as a major adverse consequence, are likely to decrease or even suppress ecological connectivity among populations of aquatic organisms and organisms dependent upon seasonally flooded environments. This article complements our previous results by assessing the relationships between dams, our Dam Environmental Vulnerability Index (DEVI), and the biotic environments threatened by the effects of dams. Because of the cartographic representation of DEVI, it is a useful tool to compare the potential hydrophysical impacts of proposed dams in the Amazon basin with the spatial distribution of biological diversity. As the impact of Amazonian dams on the biota of both rivers and periodically flooded riparian environments is severe, DEVIs from different Amazonian tributary basins are contrasted with patterns of diversity and distribution of fish, flooded forest trees and bird species. There is a consistent relationship between higher DEVI values and the patterns of higher species richness and endemism in all three biological groups. An assessment of vulnerability at the scale of tributary basins, the assessment of biodiversity patterns related to DEVI, and the analysis of teleconnections at basin scale, demonstrate that recent construction of dams is affecting the biota of the Amazon basin. The evidence presented here predicts that, if currently planned dams are built without considering the balance between energy production and environmental conservation, their cumulative effects will increase drastically and represent a major threat to Amazonian biodiversity.